Needs Analysis of Poetry Appreciation Learning Materials Oriented Toward Culturally Responsive Teaching for University Students - Ahmad Subhan Roza; Andri Wicaksono; Yulia Siska; Trisna Dinilah Harya (Bulletin of Pedagogical Research, 2025)
This study aims to identify and understand the need for developing poetry appreciation teaching materials that are oriented towards Project Based Learning with the approach Culturally Responsive Teaching (CRT)The needs analysis includes curriculum and teaching materials analysis, student questionnaire analysis, and lecturer interview results. The results of this analysis are expected to form the basis for development. Textbook for Literary Appreciation in Elementary Schools that meet learning needs. The method used is a qualitative descriptive approach, namely analyzing the needs of lecturers and students for Poetry Appreciation teaching materials in elementary schools. Data collection techniques used interviews and questionnaires. The development of these teaching materials began with a needs analysis activity oriented towards students. Project Based Learning (PBL) with the approach Culturally Responsive Teaching (CRT), followed by formulation of objectives, analysis of student characteristics, analysis of materials, determination of cultural aspects, program development, trials, and revisions. The results of the study indicate that students of the Elementary School Teacher Education Study Program need teaching materials according to student needs in learning Literary Theory and Appreciation in Elementary Schools on the material of Poetry Appreciation